MANUSIA DAN POTENSI PENDIDIKANNYA; PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Muhammad Hasbi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
Human being has a potential capacity to determine themselves with their own efforts to make education became their alternative choice to actualize themselves. In education process, human being position are always put as a starting point and ultimate goal becuase it is as their main goal of education. Islamic education phyloshopy clearly discusses human in Islamic concept. Human in islamic education is a unity of physical components, and the third components in every human lives as their potential support to retain their lives better. So, it must be supported with a such kind of media which is called education. With education, many kinds of potention can make a true Islamic human as the follower and messeger of Allah.